Two novel heterozygote missense mutations of the ADAMTS13 gene in a child with recurrent thrombotic thrombocytopenic purpura - Rossio, Raffaella (Edizioni SIMTI - SIMTI Servizi Srl, 2013)
BACKGROUND: Thrombotic thrombocytopenic purpura is a rare, life-threatening disease characterised by microangiopathic haemolytic anaemia, thrombocytopenia and symptoms related to organ ischaemia, mainly involving the brain and the kidney. It is associated with a deficiency of ADAMTS13, a plasma metalloprotease that cleaves von Willebrand factor. The congenital form (Upshaw-Schulman syndrome) is rare and is associated with mutations of the ADAMTS13 gene on chromosome 9q34. The clinical symptoms of congenital thrombotic thrombocytopenic purpura are variable, with some patients developing their first episode during the neonatal period or childhood and others becoming symptomatic in adulthood. MATERIALS AND METHODS: We describe a case of thrombotic thrombocytopenic purpura, who presented to our attention with a relapsing form of the disease: the first episode occurred at the age of 13 months. Phenotype and genotype tests were performed in the patient and his family. RESULTS: The undetectable level of ADAMTS13 in the patient was caused by two novel heterozygote missense mutations on the ADAMTS13 gene: one mutation is c.788C > T (p.Ser263Phe) on exon 7 and the second is c.3251G > A (p.Cys1084Tyr) on exon 25 of the ADAMTS13 gene. All the relatives who have been investigated were found to carry one of these missense mutations in a heterozygous state. DISCUSSION: Although Upshaw-Schulman syndrome is a rare disease, it should be considered in all children with thrombocytopenia and jaundice in the neonatal period. In fact, once a child is confirmed to carry mutations of the ADAMTS13 gene causing early thrombotic thrombocytopenic purpura, prophylactic treatment should be started to avoid recurrence of symptoms. Genotype tests of relatives would also be important for those women in the family who could be carriers of ADAMTS13 mutations, particularly during pregnancy.